Surveying the Frontier: Subjective Rendering and Occlusion in Open-World Westerns - Miner, Joshua (Gamevironments, 2020)
The last decade has seen open-world design transform the western genre in video games by recentering land as a thematic and mechanical component. As a description of both environment design and gameplay, open worlds offer highly interactable spaces, made coherent by narrative despite limited spatial linearity. A subjective camera that constructs the player’s perspective aids in this coherence. This article examines subjective rendering, a modality of image synthesis that focalizes the player’s shared decision-making with rendering algorithms, arguing that this dynamic in open-world westerns configures the player’s view of Indigenous bodies and objects. Subjective rendering techniques, particularly occlusion and simplification methods that remove geometry from view, reorganize gamic vision and limit how developers can complicate the in-built ways of seeing through the renderer. Occlusion then becomes both a principle of open-world design and a technical metaphor for examining how rendering structures exploration and possibility. This raises the stakes for gamic environments in westerns: both game and player determine how a shifting landscape that is so central to the conflict between settler and Indigenous figures materializes. Alternate approaches to these questions introduce interesting claims about the logic of settler digitality, a function of the algorithmic grammar of mainstream video games. Ultimately, renderers are cultural engines, not objective ones